Knowledge of Seniors with Diabetes Mellitus about Self-Care - Mezher, Mohammed K.; Hasain, Ala’a Mirza (Journal of Science in Medicine and Life, 2024)
Background: Diabetes Mellitus is a significant global medical issue that stands out among chronic diseases due to its influence on national and international measures of morbidity and death. Objectives: The objectives of the present study were to evaluate the knowledge of diabetic old age about self-care. Method: descriptive study was conducted among 69 elderly patients with diabetes mellitus who attended the Diabetes Center in Al Muthanna City. The data collected using questionnaire, which consists of two parts. Part I: consists of demographic characteristics. Part II: consists of (5) domains about knowledge the self-care of DM. Results: The study showed that the more half of participants were aged (65-75) years with most patients were males and majority of patients (66.7%) are read and write only. about (56.5%) of responders’ resident in rural area and (81%) are insufficient monthly income. most of the participants had poor level knowledge toward self-care. Conclusion: The study concluded that the participants had a poor knowledge regarding diabetes selfcare.